Study on the changes in the temperature sensitivity of spring phenology of typical woody plants in the Qinling Mountains region - Zhang, Shanhong; Meng, Qing; Ma, Qian; Bai, Hongying; Li, Shujuan (Frontiers in Earth Science, 2025)
To reveal the responses of plant phenology and climate change in the Qinling Mountains region, the phenological data of seven woody plants in the Qinling Mountains region from 1964 to 2020 were selected to analyze the patterns and characteristics of plant phenological changes in the Qinling Mountains region and explore the factors influencing temperature sensitivity changes during the spring phenology. The results revealed the following: (1) In the 60-year study period, the spring phenology of plants in the Qinling Mountains region showed an extremely significant advancing trend, the autumn phenology showed an extremely significant delaying trend, and the growth period of phenology increased. There was consistency between the plant phenological change and climate change in the Qinling Mountains region; that is, the year of the spring and autumn phenology change was basically the same as that of the climate change. (2) The temperature sensitivity of spring phenology showed a significant decreasing trend before the abrupt change but showed an insignificant increasing trend after the abrupt change. (3) The rate of change in spring temperature was the main factor affecting the change in temperature sensitivity of spring phenology. The temperature change rate is large in spring, the sensitivity of phenological temperature decreases in spring, the temperature increases steadily in spring, and the sensitivity of phenological temperature increases in spring. (4) Changes in the temperature zone are important causes of changes in temperature sensitivity of the spring phenology.